2012
DOI: 10.1136/jmedgenet-2012-100867
|View full text |Cite
|
Sign up to set email alerts
|

Delineation ofCCDC39/CCDC40mutation spectrum and associated phenotypes in primary ciliary dyskinesia

Abstract: CCDC39 and CCDC40 mutations represent the major cause of PCD with IDA defects and axonemal disorganisation. Patients carrying CCDC39 or CCDC40 mutations are phenotypically indistinguishable. CCDC39 and CCDC40 analyses in selected patients ensure mutations are found with high probability, even if clinical or ciliary phenotypes cannot prioritise one analysis over the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 18 publications
8
42
0
1
Order By: Relevance
“…Recently, we, and others, found that recessive mutations in CCDC39 and CCDC40 cause PCD with severe ultrastructural defects such as marked tubular disorganization with displacement of peripheral outer doublets as well as the central pair apparatus and associated IDA defects 10,11,29 . Defective N-DRC and inner dynein arm assembly in CCDC39 and CCDC40 mutant cilia is characterized by absence of the DRC component GAS11 (DRC4) and the inner dynein arm light chain DNALI1 (orthologous to Chlamydomonas light chain p28) from the ciliary axonemes.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, we, and others, found that recessive mutations in CCDC39 and CCDC40 cause PCD with severe ultrastructural defects such as marked tubular disorganization with displacement of peripheral outer doublets as well as the central pair apparatus and associated IDA defects 10,11,29 . Defective N-DRC and inner dynein arm assembly in CCDC39 and CCDC40 mutant cilia is characterized by absence of the DRC component GAS11 (DRC4) and the inner dynein arm light chain DNALI1 (orthologous to Chlamydomonas light chain p28) from the ciliary axonemes.…”
Section: Resultsmentioning
confidence: 94%
“…Mutational analysis of PCD patients identified a number of families with mutations in CCDC39 and CCDC40 (6, 12, 20, 98). Immunofluorescence analysis of airway cilia samples from CCDC39 and 40 patients found a loss of GAS11, a component of the dynein regulatory complex (DRC), and DNALI1, a member of the IDA light chain family, from ciliary axonemes (12, 98).…”
Section: Human Ciliopathiesmentioning
confidence: 99%
“…Of note, subjects with DNAH11 (MIM 603339) mutations present with a clinical phenotype consistent with PCD, but with no ultrastructural defects detectable using standard transmission EM [15]. Mutations in other genes such as CCDC39 (MIM 613798) and CCDC40 (MIM 613799) produce inconsistent ultrastructural abnormalities characterized by disordered microtubules in only some respiratory cells [14], [19], [20], which underscores the limitations of EM as a diagnostic test for PCD [15].…”
Section: Introductionmentioning
confidence: 99%